2017
DOI: 10.3390/atmos8110207
|View full text |Cite
|
Sign up to set email alerts
|

Observed and Projected Precipitation Changes over the Nine US Climate Regions

Abstract: Abstract:We analyze the past temperature and precipitation changes in nine separate US climate regions. We find that the temperature increased in a statistically significant (95% confidence level equivalent to alpha level of 0.05) manner in all of these regions. However, the variability in the observed precipitation was much more complex. In the eastern US (east of Rocky Mountains), the precipitation increased in all five climate regions and the increase was statistically significant in three of them. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In general, Arizona was dominated by warming trends with insignificant changes in daily precipitation anomalies during the past two decades. Despite the paucity of (historical) climate change studies focusing exclusively on the entire Arizona, the observed patterns are found in generally good agreement with many regional studies [53][54][55][56]. For example, Garfin et al [54] pointed out that there was only little change in mean annual precipitation from 1901 to 2010; this was later confirmed by Chylek et al [53], in which no statistically significant trend was observed in the western part of the U.S.…”
Section: Climate Change and Variabilitysupporting
confidence: 80%
See 1 more Smart Citation
“…In general, Arizona was dominated by warming trends with insignificant changes in daily precipitation anomalies during the past two decades. Despite the paucity of (historical) climate change studies focusing exclusively on the entire Arizona, the observed patterns are found in generally good agreement with many regional studies [53][54][55][56]. For example, Garfin et al [54] pointed out that there was only little change in mean annual precipitation from 1901 to 2010; this was later confirmed by Chylek et al [53], in which no statistically significant trend was observed in the western part of the U.S.…”
Section: Climate Change and Variabilitysupporting
confidence: 80%
“…Remote Sens. 2020, 12, x FOR PEER REVIEW 11 of 26 confirmed by Chylek et al [53], in which no statistically significant trend was observed in the western part of the U.S.…”
Section: Vegetation Change and Variabilitymentioning
confidence: 86%
“…During the 20th century, intensification of the global hydrological cycle has been observed [1], and the trend is expected to continue under a warming climate [2]. The established robust responses of the global hydrological cycle to temperature rise include amplified variance of precipitation everywhere [3], increased precipitation intensity over land [4,5], land evapotranspiration acceleration [6], and reduced soil moisture [7]. The long-term decline in soil moisture is the only response that has not been validated against in-situ measurements, as historical ground observations are limited [8] and soil moisture products derived from satellites are sensitive to the accuracy of retrieval algorithms [9,10].…”
Section: Introductionmentioning
confidence: 99%